2019
DOI: 10.1080/09546634.2018.1480746
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and survival of biologic agents in psoriasis: a practical real-life 12-year experience in a French dermatology department

Abstract: In a long-term real-life setting, drug survival of ustekinumab is better than that of TNF-a inhibitors for both biologic-naive and biologic-experienced patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…Prospectively collected registry data in the U.K., primarily from the British Association of Dermatologists Biologics and Immunomodulators Register, and focused on biologic‐naive patients with psoriasis, demonstrate that survival of response with biologic therapies decreases over time from 77% in the first year to 53% in the third year . Studies in other countries have shown similar results …”
Section: Summary Of Patient Characteristics and Response To Biologicsmentioning
confidence: 83%
“…Prospectively collected registry data in the U.K., primarily from the British Association of Dermatologists Biologics and Immunomodulators Register, and focused on biologic‐naive patients with psoriasis, demonstrate that survival of response with biologic therapies decreases over time from 77% in the first year to 53% in the third year . Studies in other countries have shown similar results …”
Section: Summary Of Patient Characteristics and Response To Biologicsmentioning
confidence: 83%
“…e mean age at IFX introduction was 58.7 (32-83), and IFX was introduced as a late line of systemic therapy (mean 4.5 lines). e mean duration of IFX treatment was 8.5 years (6)(7)(8)(9)(10)(11)(12). In terms of comorbidities, dyslipidemia was observed in 15 patients (35%), and depressive disorders were treated in 13 patients (30%).…”
Section: Resultsmentioning
confidence: 99%
“…Although the prevalence of long-term IFX-treated patients is not known, previous studies demonstrated a drug survival of IFX inferior to 20% at 6 years [4,6]. In our series, we calculated a prevalence of 14% of patients who were treated with IFX for longer than 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В лечении псориаза тяжелой и средней степени тяжести успешно используются биологические агенты, прежде всего ингибиторы ФНО-α: инфликсимаб, адалимумаб, этанерцепт [59]. Данные, касающиеся неблагоприятных почечных эффектов в ответ на биологическую терапию, включают единичные описанные клинические случаи аутоиммунного поражения почек у пациентов с различными заболеваниями, включая псориаз [60,61].…”
Section: лекарственно-индуцированное поражение почек при псориазеunclassified